Mejora aplicada en la empresa SOLAGRO S.A.C. mediante el uso de herramientas de Lean Manufacturing - Abadia Rios, Marjory (2021)
The Solagro company has not had the objectives expected by management during the years 2017, 2018 and 2019, in which it presents gross margins of 15%, 12% and 11%, which are lower than the goal of 20%. It is proposed to apply Lean tools to propose a solution to the main problem. By performing an analysis of the current situation through a Value Stream Map (VSM), it has been possible to identify waste in the production process and, together with a cause-effect relationship diagram and with the support of the analysis tool "Thibaut", the root causes of the main problem "Delay in Production" were identified. From these causes, different solution alternatives were proposed. From the analysis of qualitative and quantitative factors, a Lean tool called Heijunka was chosen. Due to the seasonality of the demand, it was proposed to develop a quarterly Heijunka. This proposal is complemented with the assurance of the same through the development of 4 annual trainings to the operators, in addition to quarterly inspections that will aim to evaluate critical control points at each stage of the production process. As a result of the improvement, there will be a B / C of 2,66 soles and a NPV of 736 044,02 soles, which, being positive, indicates the viability of the project. Likewise, the “ARENA” software was used, which allowed simulating the current and future scenarios of the project, in this way a reduction in the lead time of the process was demonstrated by 98,47%. The risk assessment carried out using the @Risk tool allowed us to know that the improvement project is viable because, with a confidence interval of 90%, the NPV will always be positive and the IRR will be greater than the COK. While the variable with the greatest impact on the model is the Price.